Shaping Entrepreneurial Futures: Educational and Contextual Predictors among Vocational Tourism Students - Sutono, Anang; Masatip, Anwari; Sugiama, Aceng Gima; Sudono, Agus (Journal of Tourism, Hospitality and Travel Management, 2024)
Entrepreneurial intention among vocational tourism students has emerged as a critical focus in promoting job creation and self-employment in the creative economy sector. This study aims to examine the direct effects of entrepreneurial education, learning experience, industry openness, and digital efficacy on students' entrepreneurial intention while also evaluating the psychological roles of self-efficacy and attitude toward entrepreneurship. Employing a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS), data were collected from 278 vocational tourism students in Indonesia through an online survey. The results indicate that entrepreneurial education significantly influences both self-efficacy and entrepreneurial attitude. Learning experience positively impacts self-efficacy, while industry openness demonstrates a strong direct effect on entrepreneurial intention. Digital efficacy does not directly affect self-efficacy or intention but contributes positively to entrepreneurial attitude. Conversely, self-efficacy does not have a significant direct effect on intention, whereas attitude toward entrepreneurship does. These findings extend the application of the Theory of Planned Behavior (TPB) by integrating contextual factors related to vocational education and provide strategic insights for curriculum designers and policymakers aiming to enhance the entrepreneurial capacity of vocational tourism institutions.